Is telemedicine a golden opportunity or a dangerous roundabout for chronic rheumatic diseases? A narrative review (Interdisciplinary Journal of Nursing and Health, 2022)
Introduction: Telemedicine (TM) reported a great increase from 50% to 150% in health care to RMDs patients during the COVID-19 period, but conflicting opinions in the literature are still present.Aim: to investigate the results of literature on TM in terms of feasibility (patients’ satisfaction, accessibility, clinical outcomes and barriers), discussing its integration for the future in a nursing perspective during and after COVID-19 period.Methods: the team that conducted the narrative review was composed by two rheumatology and research nurses (MRM, KEA) and a rheumatologist (MMC), who discussed the relevance of the research question and agreed on the search strategy. Pubmed and Google Scholar databases were searched. The inclusion criteria were: original and quantitative research papers in English with available abstract/full text, on adult patients with RMDs in accordance with the American College of Rheumatology (ACR) and/or European Alliance of Associations of Rheumatology (EULAR) classification criteria, exposed to any kind of technologies during and after COVID19 period, investigating any kind of patient/clinical reported outcomes.Results: TM could be considered as an integration to standard clinical care in Rheumatology, especially for patients with a stable or low disease activity and rheumatic diagnosis. The choice of the candidates and the assessment of their E-health literacy level are necessary prior including them in TM programs. In addition, healthcare professionals need to be trained in this new modality of providing care.Conclusion: hybrid models of telehealthcare might be a balanced solution, improving efficiency of the consultation, continuity of care and providing a patient-centred approach.
Keywords: telerheumatology; telemedicine; telenursing; COVID-19; rheumatic diseases; rheumatic and musculoskeletal diseases